PENGUKURAN JUMLAH LIMFOSIT CD4 METODE PANLEUCOGATING PADA PASIEN TERINFEKSI HUMAN IMMUNODEFICIENCY VIRUS (HIV) - Umi S. Intansari; Budi Mulyono; Usi Sukorini (Indonesian Association of Clinical Pathologist and Medical laboratory, 2013)
The standard method for absolute lymphocyte CD4 count is by the use of flow cytometric analysis, but due to the high costly matter,a simpler method and less costly fee of PanLeucogating dual platform is needed. The aim of this study is to know how to replace the single platform by PanLeucogating dual platform by determining the agreement between both methods and to test the proportion of patient who have CD4 <200 cell/ul measured by PanLeucogating and single platform method. A cross sectional study was carried out in the Departement of Clinical Pathology Faculty of Medicine Gadjah Mada University Yogyakarta. The inclusion criteria of the study are HIV/AIDS patients who their CD4 were measured. Absolute count of CD4 was using FACS Calibur measured with both PanLeucogating and single platform method. The bias, correlation, regression and limit of agreement between both methods were analyzed using Bland Altman analysis to decide whether the two methods are interchangeable. The result of the study revealed an excellent correlation between the two methods (r=0.996; y=- 0.906 + 0.0.987). Bland Altman analysis revealed bias=5 cells/uL; standard deviation=18.7 and Limit of agreement (LOA)=-31.6 – 40.75. The Mean Percentage Difference (MPD)=2%; dan%LOA=-7.96 – 12.5%. PanLeucogating method has a good agreement with the single platform method and can be used interchangeable. There was no difference of the proportion of patient who has CD4 <200 cell/ul measured by Panleucogating method and single platform.